2011
DOI: 10.2217/nnm.11.62
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanotube-Mediated Wireless Cell Permeabilization: Drug and Gene Uptake

Abstract: The results showed that MAN has desirable in vivo biocompatibility, presenting potential for use as a MDDS, especially in CNS disease therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 90 publications
1
9
0
2
Order By: Relevance
“…47 A recent report suggested that exposure to electromagnetic waves promotes CNT entry not only into the cytoplasm of cells, but also into the nucleus. 50 Our present findings suggest a similarity between the modes of action of humic macromolecules with analogous biomacromolecules/proteins. The macromolecule acts as shuttle-like agent to enhance the permeability of [CNT/ organic] into the internal cellular compartments.…”
Section: A Physicochemical Mechanismsupporting
confidence: 63%
“…47 A recent report suggested that exposure to electromagnetic waves promotes CNT entry not only into the cytoplasm of cells, but also into the nucleus. 50 Our present findings suggest a similarity between the modes of action of humic macromolecules with analogous biomacromolecules/proteins. The macromolecule acts as shuttle-like agent to enhance the permeability of [CNT/ organic] into the internal cellular compartments.…”
Section: A Physicochemical Mechanismsupporting
confidence: 63%
“…Excitation of CNTs by exposure to an appropriately tuned radio frequency field has been shown to permeabilize cell membranes to allow cell uptake of normally impermeable drugs or gene expression vectors both in in vitro and in vivo in brain tissue [101]. Similarly, treatment of cancer cells or tumor bearing mice using SWNTs chemically conjugated with platinum-based chemotherapeutics [102] or loaded with doxorubicin by hydrophobic interactions [103] and combined with NIR mediated photothermal heating were significantly more effective than either therapy alone.…”
Section: Cnt-mediated Thermal Therapy: Rationale and Current Statusmentioning
confidence: 99%
“…Similarly, oxidative stress-induced DNA damage was also observed after an intraperitoneal administration of IONPs in mice 18,40 . However, few studies also reported no genotoxicity induced by IONPs 41,42 . In our study, we found that IONPs exposure to Wistar rats increases the frequency of both chromosomal aberration and micronucleus induction along with increased DNA damage in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%